Evaluating the Systems Engineering Problem Management Process for Industrial Manufacturing Problems. Issue 2 (6th June 2016) - Perry, Dennis A.; Olson, Bill; Blessner, Paul; Blackburn, Timothy D.
ABSTRACT: Problems are ever‐present in nearly all engineered systems. A Systems Engineering Problem Management Process (SEPMP) has been proposed, and this research presents empirical evidence to support its validity. In order to evaluate the SEPMP, which uses a risk management style matrix to monitor problem timeliness and impact, it is necessary to determine the importance of communicating these components of the SEPMP model. A correlation and regression analysis is employed using existing empirical problem data and an analysis including communication of impact and timeliness components as independent variables. The dependent variable is the effectiveness of problem management, modeled as a measurement of the problem timeliness, implemented process improvements, training completed, and process delay as a result of the problem. Communication of timeliness and communication of impact are demonstrated to be significantly predictive of effective problem management. Finally, a plan for continued research is presented, including suggested future analyses to include additional empirical research and case studies of the implementation of a comprehensive problem management process, all of which may encourage acceptance of the SEPMP as a standard systems engineering tool.